Translation Techniques of Dialogues in Pramoedya Ananta Toer’s ‘The Girl from the Coast’ by Willem Samuels - Angely, Marcel Dewi; Novalinda, Novalinda (LingoLitera, 2026)
This study discusses the translation techniques used in translating the dialogue in the novel ‘The Girl from the Coast’ by Pramoedya Ananta Toer, translated by Willem Samuels. The purpose of this study is to analyze the translation techniques used in translating the dialogue in the novel ‘The Girl from the Coast’ and the most dominant techniques used. The theory used in this study is the 18 translation techniques proposed by Lucia Molina and Amparo Hurtado Albir (2002). The methods used in this study are qualitative, involving reading, collecting data, and describing the findings. Data was collected from the dialogue of the novel ‘The Girl from the Coast’, specifically in chapter 1. From this research, there were 12 out of 18 translation techniques used to translate the dialogue in the novel. These techniques are adaptation (6 data), amplification (33 data), borrowing (2 data), compensation (2 data), description (1 data), generalization (11 data), linguistic amplification (5 data), literal translation (20 data), modulation (15 data), particularization (4 data), reduction (12 data), dan transposition (4 data). The most dominant technique is the amplification technique, and the least frequently used technique is the description technique.